PENGARUH MOTIVASI BERPRESTASI, KEPUASAN KERJA, DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN PADA PT. TIRTA INVESTAMA DI MAMBAL - I Kadek Pandu Adi Santika; I Wayan Sujana; Ni Nyoman Ari Novarini (VALUES, 2022)
This study aims to examine and obtain empirical evidence of the effect of achievement motivation, job satisfaction, and transformational leadership on employee performance at PT. Tirta Investama in Mambal. The population in this study was all employees at PT. Tirta Investama in Mambal as many as 45 employees. The sampling technique used a saturated sample, so that 45 people were used as samples by taking random sampling. The analytical tool used is multiple linear analysis. The results of this study indicate that achievement motivation has a positive and significant effect on employee performance at PT. Tirta Investama in Mambal. Job satisfaction has a positive and significant effect on employee performance at PT. Tirta Investama in Mambal. Transformational leadership has a positive and significant effect on employee performance at PT. Tirta Investama in Mambal. It is recommended to the leadership of PT. Tirta Investama in Mambal to give awards to employees who excel so that the employee's sense of pride increases and is more responsible for their work.